THE EFFECT OF SOCIAL AND ECONOMIC VARIABLES ON BEHAVIORAL AND EMOTIONAL DISORDERS - Bintang Satrio Wibowo (KENDALI: Economics and Social Humanities, 2025)
This study investigates the impact of socioeconomic factors on individuals' behavioral and emotional health using data from the Indonesian National Socioeconomic Survey (SUSENAS). Employing a Multinomial Logistic Regression approach, the analysis reveals that marital status significantly influences mental well-being, with married individuals generally exhibiting a lower probability of experiencing behavioral and emotional problems compared to those who are unmarried or divorced. Economic indicators such as per capita expenditure and educational attainment are found to have a negative and significant association with the likelihood of such disorders, suggesting that higher socioeconomic status contributes to better psychological outcomes. Conversely, residing in urban areas is positively associated with increased risk, possibly due to environmental stressors such as pollution, social pressure, and population density. The study acknowledges limitations related to the exclusion of psychological and environmental factors that may also affect mental health outcomes. These findings underscore the importance of integrating socioeconomic dimensions into mental health policy frameworks and highlight the need for targeted, community-based preventive interventions, particularly for urban populations and individuals without spousal support.